VERIFICATION OF BUILDING RECOGNITION WITH EXPERT DATA - Соколова, Наталья (SWorldJournal, 2020)
Automatized building recognition is one of the principal aspects of Earth remote sensing data processing. This article describes an information processing technology of building recognition in high spatial resolution photogrammetric images. Specifically